A coordinated study of field-aligned currents and Pc5 ULF waves during ejecta 1997 - Bochev, A. Z.; Sinha, Ashwini K. (My University, 2010)
We show examples of long period Pc5 magnetic field pulsations near field-aligned current (FAC) regions in the high-latitude magnetosphere, observed by INTERBALL-Au, and coordinated with POLAR, GOES-9 and ground-based observations during 11 January and 11 April 1997. Identification of corresponding magnetosphere regions and subregions is provided by electrons and protons in the energy-range of 0.01–100 keV measured onboard the spacecraft. TheULFPc5 wave occurrence is observed in both upward and downward FACs.Afairly good correlation is demonstrated between these ULF Pc5 waves and the onsecutive injection of magnetosheath low energy protons. The constancy of the observed frequency peak at 1.8 mHz during quite unsteady solar wind pressure conditions could be reconciled with the surface wave mode model. The 3.1 mHzpeak location area probably resembles field-line fluctuations with an interesting appearance of poloidal mode oscillation. It is suggested that the 1.3 mHz wave and its harmonic 2.6 mHz represent global compressional oscillations.
Keywords: Field-aligned currents; ULF wave-Pc5 pulsations; Compressional oscillations; INTERBALL spacecraft